De Kooning an American master - Stevens, Mark (Knopf, 2004)
Traces the career of abstract expressionist Willem De Kooning, discussing his personal life with wife Elaine Fried, and his battle with alcoholism and Alzheimer's disease.
Includes bibliographical references and index
Keywords: De Kooning, Willem <1904-1997>; De Kooning, Willem <1904->; Kooning, Willem de <1904-1997>; De Kooning, Willem -- 1904-1997; Artistes - États-Unis - Biographies; Kunstschilders; Artists -- United States -- Biography; USA; Biografie; Biographie (Descripteur de forme)